The effect of fraud, condition and error in marital consent: some personalist considerations - Burke, Cormac (Monitor ecclesiasticus, 1997)
Dolus, condicio de futuro und error in qualitate personae wird im Zusammenhang mit dem Ehekonsens betrachtet; Fortsetzung des Artikels ebd. S. 295-310. FR KAN Z II 65